Is Outpatient Cognitive Remediation Therapy Feasible to Use in Randomized Clinical Trials for Anorexia Nervosa? - Lock, James (2013)
OBJECTIVE: There are limited data supporting specific treatments for adults with anorexia nervosa (AN). Randomized Clinical Trials (RCTs) for adults with AN are characterized by high attrition limiting the feasibility of conducting and interpreting existing studies. High dropout rates may be relatedt to the inflexible and obsessional cognitive style of AN patients. This study evaluated the feasibility of using Cognitive Remediation Therapy (CRT) to reduce attrition in RCTs for AN. METHOD: Forty-six participants (mean age of 22.7 years and mean duration of AN of 6.4 years) were randomized to receive 8 sessions of either CRT or CBT over 2 months followed by 16 sessions of CBT for 4 months. RESULTS: During the two month CRT vs. CBT treatment, rates of attrition were lower in CRT (13%) compared to CBT (33%). There were greater improvements in cognitive inefficiencies in the CRT compared to the CBT group at the end of two months. There were no differences in other outcomes. CONCLUSION: These results suggest that CRT is acceptable and feasible for use in RCTs for outpatient treatment of AN. CRT may reduce attrition in the short term. Adequately powered future studies are needed to examine CRT as an outpatient treatment for AN.